Black Parents’ and Caregivers’ Perceptions and Decision-Making Regarding an Attention Deficit Hyperactivity Disorder Diagnosis: Implications for Intervention Pursuits. - Moyo, Beatrice (University of the Witwatersrand, Johannesburg, 2024)
Despite the increase of attention deficit hyperactivity disorder (ADHD) prevalence in South Africa, many Black parents and caregivers have been observed to struggle with accepting an ADHD diagnosis for their child. Various influences impact parental and caregivers’ ADHD perceptions, hence influencing their decision-making regarding intervention pursuits and preferences for their child diagnosed with the disorder. This study aimed to examine the perspectives of Black parents and caregivers regarding ADHD diagnosis for their children. The study also aimed to understand the significance of this diagnosis for parents and caregivers, their decision-making process, and their preferences and willingness toward different intervention options. The theoretical framework encompassed a discussion of Bronfenbrenner’s bioecological systems theory to understand, within the model of the multi-dimensional structure, different levels of influence that shape Black parents’ and caregivers’ perceptions regarding an ADHD diagnosis for their child and the implications on intervention decision-making and preferences. The study utilized an explorative and qualitative Interpretative Phenomenological Analysis (IPA) approach, focusing on the participants’ subjective experiences. Twenty-one Black parents and caregivers of four to 17- year-old children with a confirmed ADHD diagnosis were recruited from the Gauteng region in South Africa through non-probability purposive sampling. Data was collected through semi-structured face-to-face, telephonic, and online individual interviews and focus groups. Interviews and focus group discussions were audio-recorded, manually transcribed, and analyzed by the researcher. The findings highlighted a lack of ADHD awareness and knowledge among the participants. It emerged from the findings that many participants had not initially perceived their children’s ADHD-related behaviors as impairing; however, they had perception shifts through exposure to ADHD. The findings revealed that participants 6 experienced varying adverse psychological responses to their children’s ADHD diagnoses. However, nearly all the participants displayed receptiveness to the diagnoses. Participants’ understanding of the etiology and nature of ADHD for their children was shaped by several influences: ‘culture,’ ‘awareness and knowledge,’ ‘religious and spiritual beliefs,’ ‘stigma,’ ‘the role of school,’ and ‘sources of support,’ which shaped various beliefs on the management of the disorder. The study revealed that the school played a significant role in the identification of ADHD-type behaviors in children. Yet, many participants perceived that many mainstream schools were neither conducive nor accommodating of children with the disorder. Participants formed positive and negative meanings from experiences arising from their children’s behaviors and diagnoses. The meanings contributed to decisions to seek interventions for their children. A noteworthy finding from the study was the unreserved willingness displayed by participants to pursue ADHD interventions for their children, with many employing a multi-approach to ADHD management, including pharmaceutical interventions. However, the study highlighted key hindrances to intervention compliance and adherence, namely, ‘lack of awareness and limited knowledge,’ ‘parental perceptions’ about recommended interventions, and ‘limited resources.’ Keywords: Attention deficit hyperactivity disorder (ADHD); parents’ and caregivers’ perceptions; parenting & child discipline; intervention pursuits; Black African cultural influences; interpretative phenomenological analysis (IPA).
A research report submitted in partial fulfillment of the requirements for the degree of Doctor of Philosophy in Psychology to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Parents’ and caregivers’ perceptions; Parenting & child discipline; UCTD; SDG-3: Good health and well-being